2006
DOI: 10.1038/sj.gt.3302824
|View full text |Cite
|
Sign up to set email alerts
|

Local gene transfer to calcified tissue cells using prolonged infusion of a lentiviral vector

Abstract: Gene transfer using viral vectors offers the potential for the sustained expression of proteins in specific target tissues. However, in the case of calcified tissues, in vivo delivery remains problematic because of limited accessibility. The aim of this study was to test the efficiency of lentiviral vectors (LVs) on osteogenic cells in vitro, and determine the feasibility of directly transducing resident bone cells in vivo. LVs encoding for green fluorescent protein (GFP) and ameloblastin (AMBN), a protein ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
(77 reference statements)
0
15
0
Order By: Relevance
“…Lentiviruses have been used and showed that they can infect osteoblasts with high efficiency in vitro. When directly applied in vivo into surgically created lesions of the mandible and tibia, lentiviruses were found to infect most cell types present in bone, especially in the regenerating chondrocytic callus of the tibia (Wazen et al, 2006). A recent study showed success with lentiviral vectors as delivery system for shRNAmediated RNA interference in MC3T3 cells (Moffatt et al, 2008).…”
Section: Rna Interferencementioning
confidence: 99%
“…Lentiviruses have been used and showed that they can infect osteoblasts with high efficiency in vitro. When directly applied in vivo into surgically created lesions of the mandible and tibia, lentiviruses were found to infect most cell types present in bone, especially in the regenerating chondrocytic callus of the tibia (Wazen et al, 2006). A recent study showed success with lentiviral vectors as delivery system for shRNAmediated RNA interference in MC3T3 cells (Moffatt et al, 2008).…”
Section: Rna Interferencementioning
confidence: 99%
“…Moreover, it has to be mentioned that for immunotherapy, the lentiviral vectors are systemically administered, whereas in the case of gene therapy, the lentiviral vectors are most often administered in the Lentiviral vectors in cancer immunotherapy K Breckpot et al tissue of interest, resulting in transduction of these tissue-specific cells. [157][158][159][160][161] Second, when using ex vivo-transduced DC or targeting DC in vivo, terminally differentiated, nondividing cells are transduced as opposed to extensively proliferating cells in the SCID trial, thereby posing less of a risk for oncogenic transformations. Finally, when an immune response is induced in vivo, the effector cells will most likely kill cells that express the target antigen, including the transduced APC, thus, further reducing the risk for oncogenesis.…”
Section: Concerns In View Of Lentiviral Vectors As Anticancer Vaccinementioning
confidence: 99%
“…An NheI-BamHI restriction fragment encompassing the PKAdn cDNA and the c-Myc tag was subcloned into pLVX-IRES-Puro between the SpeI and BamHI restriction sites of the pLVX vector. Lentivirus production and cell infection were performed as previously described (27 SDS, 5 mM EDTA, 2.5 mM sodium pyrophosphate, 1 mM ␤-glycerophosphate, 1 mM sodium orthovanadate, and 1 g/ml leupeptin, 1 g/ml aprotinin, 1 mM phenylmethylsulfonyl fluoride protease inhibitors). For immunoprecipitation (IP), the cells were collected in IP buffer (20 mM Tris-HCl [pH 7.5], 150 mM NaCl, 1 mM EDTA, 1 mM EGTA, 1% Triton X-100, 2.5 mM sodium pyrophosphate, 1 mM ␤-glycerophosphate, 1 mM sodium orthovanadate, with protease inhibitors).…”
Section: Methodsmentioning
confidence: 99%